PENINGKATAN KESADARAN GIZI SEIMBANG PADA REMAJA MELALUI EDUKASI DI MAN 1 BANDAR LAMPUNG - Sulya, Hana; Marta, Annisa Tiara; Jausal, Anisa Nuraisa; Maulana, Muhammad; Iyos, Rekha Nova; Wardhana, Muhammad Fitra (JPM (Jurnal Pengabdian Masyarakat) Ruwa Jurai, 2025)
Adolescents are a vulnerable age group prone to nutritional problems due to a lack of knowledge and awareness regarding healthy eating patterns and the importance of limiting sugar intake. This condition increases the risk of non-communicable diseases such as obesity, diabetes mellitus, and hypertension from a young age. This community service activity was carried out as part of the work program of the Community Service Department, BEM FK Unila, under the "Health Day" initiative in commemoration of World Health Day 2025, with the subtopic of balanced nutrition in adolescents. The service included educational outreach through a podcast on balanced nutrition for adolescents, health counseling, and health checks (blood sugar and anthropometric measurements) for students and teachers at MAN 1 Bandar Lampung. The results showed high participant enthusiasm and increased adolescent understanding of the importance of balanced nutrition and the dangers of excessive sugar consumption. This activity demonstrated that an educational approach using media and direct health screening is effective in raising nutritional awareness among adolescents. Ongoing counseling is recommended to strengthen the development of healthy lifestyle habits starting from school age.